Pengenalan Sistem Pencernaan Anatomi Tubuh Manusia Pada Anak Prasekolah TK MGI Ciamis - Sandriani Sandriani; Sri Utami Asmarani; Sri Wulan Ratna Dewi; Ayu Endang Purwati; Metty Nurherlyany; Neli Sunarni; Resna Litasari (Daarul Ilmi: Jurnal Pengabdian Kepada Masyarakat, 2025)
Introduction: Young children have extraordinary learning abilities, especially in early childhood. The function of stimulus for early childhood is to provide various efforts for children's basic knowledge. The digestive system is one of the vital organ systems that processes food into substances useful for children's growth, energy, and health, so a basic understanding of this system is relevant to introduce from an early age. Through creative, interactive, and fun educational strategies supported by innovative learning media and age-appropriate scientific approaches, it is hoped that children can build a better understanding of the human digestive system and sustainable healthy living behaviors. Objective: The objectives of this community service program are to improve children's basic knowledge of anatomy and the digestive system, encourage children's interest in learning and curiosity about science, develop basic health awareness in children from an early age, and provide support and resources to teachers in teaching science creatively. Method: The methods used in implementing this activity were lectures, discussions, question and answer sessions, and demonstrations with 168 participants aged 5-6 years old on average. Result: The implementation of the activity showed that preschool children at MGI Ciamis Kindergarten responded very positively to the material introducing the anatomy of the body and the digestive system. After being educated through play-based learning methods, demonstrations using anatomical models, visual media, and picture stories, there was a gradual increase in the children's understanding. Conclusion: The community service program has been successfully implemented and has made a positive contribution to improving early childhood understanding of the human body and the digestive system. In addition to benefiting children, this community service program has also benefited teachers and the school environment, particularly in enriching basic health and science teaching methods and media at the preschool level.